(untitled) (Bangladesh Journal of Medicine, 2022)
Background: ABO and Rh blood group antigens are inherited traits ,located on chromosome 1 and19. They are usually not altered throughout the life of an individual. Blood grouping consists of forward grouping and reverse grouping and both procedures should match with each other. A blood group discrepancy exists when results of forward grouping and reverse grouping do not match each other. ABO and Rh blood group discrepancy should be resolved before transfusion and blood group to be properly labeled to prevent transfusion reaction. Methods: A prospective study was carried out in Department of Transfusion Medicine and Blood Bank , National Institute of Kidney Diseases & Urology (NIKDU), Dhaka Bangladesh from January 2014 to Dcember-2016. Total 50 blood samples from SLE patients were included in the study . The ABO and Rh D typing was done by tube technique using monoclonal IgM (oeShield Diagnostic ,UK) Anti-A, Anti-B, Anti-AB and pooled A, B and O cell and Anti-D. Results: A total of 50 blood group testing were done where we found 50 blood group discrepancies with overall frequency was 100% and transfused safely. Conclusion: Any discrepancy between forward and reverse blood grouping methods should be resolved before transfusion of blood components. Bangladesh J Medicine 2022; 33: 202-209